2000
DOI: 10.1590/s1516-31802000000400002
|View full text |Cite
|
Sign up to set email alerts
|

Prognosis related to staging systems for chronic lymphocytic leukemia

Abstract: a b s t r a c tCONTEXT: Chronic lymphocytic leukemia (CLL) is a clonal lymphoproliferative disorder, characterized by B lymphocytic proliferation. CLL is the most frequent adult leukemia in Western countries, accounting for 25 to 30% of all white leukemic patients. OBJECTIVE:To evaluate clinical and staging characteristics in prognosis of chronic lymphocytic leukemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
1
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 25 publications
(12 reference statements)
0
2
1
1
Order By: Relevance
“…However, our study showed no significant relationship between survival of CLL patients and Rai staging. This finding is inconsistent with results ofde Faria et al 24 study in Brazil which reported a significant association between advanced Rai staging of patients with CLL and shorter survival. This inconsistency might be due to difference in health infrastructure and discrepancy in diagnostic techniques between Hemato/oncology center s of different countries.…”
Section: Discussioncontrasting
confidence: 92%
“…However, our study showed no significant relationship between survival of CLL patients and Rai staging. This finding is inconsistent with results ofde Faria et al 24 study in Brazil which reported a significant association between advanced Rai staging of patients with CLL and shorter survival. This inconsistency might be due to difference in health infrastructure and discrepancy in diagnostic techniques between Hemato/oncology center s of different countries.…”
Section: Discussioncontrasting
confidence: 92%
“…These findings partially agree with those previously reported by Shvidel et al; however, they contradict de Faria et al 's study. 27,28 The difference between these findings is probably due to variations in sample size, the lack of genetic assessment conducted in the current study and the well-known impact of ethnicity. 13 In addition, data regarding CD49d and ZAP70 expression, which have a major prognostic impact on CLL patients, were not available.…”
Section: Discussionmentioning
confidence: 67%
“…But in very studies clear finding of male predominance was stable. Which might be linked to genetic bases as revealed by results described by Cantu ES, McGill JR et al (Cantú et al, 2013) In (Faria et al, 2000) , (Pflug et al, 2014). But according to the data from previous study of Iraq most of patients existing at an advance stage such as Rai stage III or IV (59.1%) Binet stage C (55.2%) (Hasan, 2018), (Naji, 2012).…”
Section: Discussionmentioning
confidence: 97%